Staphylococcus aureus Colonization Modulates Tic Expression and the Host Immune Response in a Girl with Tourette Syndrome - Eftimiadi, Costantino; Eftimiadi, Gemma; Vinai, Piergiuseppe (Frontiers in Psychiatry, 2016)
A 9-year-old girl with Tourette syndrome and increased antibody levels against Streptococcus pyogenes was monitored longitudinally for the presence of nasopharyngeal bacteria, specific antibody titers, and autoimmunity directed against brain antigens. Microbiological monitoring indicated that the child was an intermittent Staphylococcus aureus nasopharyngeal carrier. Clinical improvements in motor tic frequency and severity were observed during the S. aureus colonization phase, and were temporally correlated with the downregulation of anti-streptococcal and anti-D1/D2 dopamine receptor antibody production. After decolonization, clinical conditions reverted to the poor scores previously observed, suggesting a possible role of the immune response in bacterial clearance as a trigger of symptom recrudescence. These findings imply that a cause-effect relationship exists between S. aureus colonization and tic improvement, as well as between bacterial decolonization and tic exacerbation. Understanding the impact of S. aureus on the host adaptive immune response and the function of autoantibodies in the pathogenesis of Tourette syndrome may alter approaches for managing autoimmune neuropsychiatric and tic disorders.